It looks like you're new here. If you want to get involved, click one of these buttons!

- 30.2K All Categories
- 25.6K LSAT
- 15.8K General
- 26 Sage Advice
- 4.6K Logical Reasoning
- 1.2K Reading Comprehension
- 1.6K Logic Games
- 65 Podcasts
- 186 Webinars
- 5 Scholarships
- 191 Test Center Reviews
- 1.7K Study Groups
- 98 Study Guides/Cheat Sheets
- 2.2K Specific LSAT Dates
- 20 June 2023 LSAT
- 6 April 2023 LSAT
- 9 February 2023 LSAT
- 25 January 2023 LSAT
- 4.6K Not LSAT
- 3.8K Law School Admissions
- 8 Law School Explained
- 11 Forum Rules
- 514 Technical Problems
- 271 Off-topic

glee66
Free Trial Member

For instance, a -> (b -> c) simplifies to a + -b -> -c. What about (-a -> b) -> c. How can I simplify it?

## Comments

(-a->b)->c

because you have a conditional within a conditional. View the lessons on Demorgans laws & mastery to see a similar issue that JY solves.

But unless=negate sufficient, so negate a and sufficient, then only if= necessary

so -a->b is its only conditional, but it is a conditional that has a conditional that applies to it as well, so (-a->b) servers as the entire sufficient, and then only if ties that it together.

Hope that makes sense, these are difficult to explain, if your having issues like I said watch the videos on Demorgans law.

y -> c,

or, -c -> -y (taking contrapositive)

or, -c -> (-a -> b)

or, -c AND -a -> b

this I get:

not (A -> would be A some -B

this I'm not so sure:

not (-A ->

Any help is much appreciated!

(A -> -> C = not C -> A and not B

(not A -> -> C = not C -> not A and not B

A -> (B->C) = A and not B -> C

?

If A exists then the relation B > C kicks in. If the relation B > C cannot kick in, then A cannot exist.